Effect of thermal shock induced dislocation multiplication on the thermal conductivity of 60 vol% SiCp/Al–7Si composites. (April 2023) - Wang, Kang; Li, Wenfang; Jin, Shuoxun; Liao, Zhongmiao; Wang, Zhiyu; Xia, Yuanguang; Chen, Huaican; Wan, Bingbing; Yin, Wen; Zhai, Tongguang
Abstract: Dislocation affects the thermal conductivity and coefficient of the thermal expansion of high-volume fraction SiCp /Al composites. However, it still remains unclear to what extent the dislocation density in the composite would be increased by thermal shock. Herein, the as-cast 60 vol% SiCp /Al–7Si composites produced via the gas-infiltration technique possess a relatively low porosity but significant lattice misfit at the interfaces. The aqueous- and liquid nitrogen-quenching exerted on the as-cast samples can produce fractures at the SiCp /Al interfaces at different extent. The neutron diffraction technique is carried out to investigate the effect of thermal shock treatments on volume-averaged dislocation densities in the composites. Results show that the dislocation configuration of the composites with as-cast and aqueous-quenching states are similar, but different from that of the sample with a liquid nitrogen-quenching state. Compared with the as-cast composite, the aqueous-quenching and liquid nitrogen-quenching treatments cause the significant increase of dislocation density. However, it only results in a relatively slight reduction of the thermal conductivity of the aluminum matrix. This work provides some references for the dislocation density determination in the high-volume fraction metal matrix composites. Graphical abstract: Image 1 Highlights: The dislocation density of the 60 vol% SiCp /Al–7Si composites was determined using the neutron diffraction technique. The dislocation configurations of the 60 vol% SiCp /Al–7Si composites were related to the thermal shock treatment modes. The quenching treatments notably increase dislocation density of the aluminum matrix that reduce its thermal conductivity.